The Relation of Zinc Deficiency Level on Memory of School-Age Children - Setianingsih, S; Dasuki, Djaswadi; Gamayanti, Indria Laksmi (Universitas Muhammadiyah Surakarta, 2015)
More than two billion people are expected to lack of essential vitamins and minerals, especially vitamin A, iodine, iron (Fe) and zinc (Zn). Research showed positive effect of zinc supplementation on children's growth, morbidity and mortality in diarrhea and pneumonia. Zinc plays an important role in the structure and function of the brain; and zinc deficiency also has negative impact the development of cognitive functions such as attention and memory. This paper aims to determine the effect of zinc deficiency on memory in school-age children in the district of Klaten. The study used was description of analytic with quantitative approach by using cross-sectional design. The experiment was conducted in some elementaryschools (SD) in the district of Klaten. The study population was the students from 9-12 age groups in the elementary schools, which in accordance with inclusion and exclusion criteria. This study employed purposive sampling technique to represent the elementary schools of villages and towns. The determination of the samples was done by PASS softwareand the number of sample was 60. The data were analyzed by using univariable and bivariable by statistical test t-test with 95% confidence intervals. The findings showed that children with zinc deficiency had the average value of 6.1 short-term memory with SD 1.3, whereas children with normal zinc levels had the average value of 10.7 and SD 3.1. The mean difference of -4.6 with 95 % CI (-6.98 - (-2.14) and a value of p = 0.0004 or p < 0.05. The average value of long-term memory of children with zinc deficiency was 7.8 with SD 3.0, whereas the average value of children with normal zinc levels was 8.4 and SD 3.2. The difference of the mean was -0.57 with 95 % CI (-3.16 - 2.01) and a value of p = 0.658 or p > 0.05. To conclude, the average scores value of short-term memory in children with zinc deficiency was lower than the short-term memory scores in children with normal zinc levels. The average scores value of long-term memory in children with zinc deficiency was equal to the children with normal zinc levels.